Acceptance of Instagram among the millenials in UiTM Kampus Bandaraya Melaka / Abdul Wafi Zamri - Zamri, Abdul Wafi (Faculty of Business and Management, 2019)
This study aimed to examine the factors of Instagram application usage among the millenials in UiTM Kampus Bandaraya Melaka. The independent variables were social influence, trustfulness and performance based on Instagram application usage among the millenials in UiTM Kampus Bandaraya Melaka. A set of questionnaire was adopted from past research to collect the primary data from respondents about the relationship the millenials with the Instagram application usage. Convenience sampling was used for this study. A total of 110 respondents had answered the questionnaires. The overall findings of the research indicate that based on the result, that all the three indipendent variables affects the accpetance of Instagram application usage among the millenials in UiTM Kampus Bandaraya Melaka. As conclusion, we can see that the Instagram application usage is also useful in the educational medium to improve the users’ attention instead of on scrolling only for feeds that will help them increase their knowledge much more than before.